Performance management of National Sports Organisations: a holistic theoretical model - Kasale, L.; Winand, M.; Robinson, L. (Sport, Business and Management, 2018)
Purpose: Organisational performance of sport organisations has been studied over the last three decades. However, little attention was paid towards performance management (PM) compared to performance measurement. The purpose of this paper is to close this research gap by establishing a holistic perspective for PM of National Sports Organisations (NSOs) that accounts for their uniqueness, the interdependence of their operating systems and their relationship with their environments. Furthermore, this paper presents a holistic model of PM for NSOs.